CO.sub.2 transport at shallow depths in arc magmas: evidence from unique orbicular dikes in the Jurassic Bonanza arc, Vancouver Island, Canada - Morris, Rebecca; Canil, Dante (Contributions to mineralogy and petrology, 2022)
A growing body of evidence suggests the interaction between arc magmas and crustal carbonates may play a large role in outgassed CO.sub.2 at arcs. We examine magma-carbonate interactions within the shallow ( 25% calcite assimilation, producing up to 11 wt% CO.sub.2, orders of magnitude higher than the CO.sub.2 solubility of the parent melt (0.11 wt% CO.sub.2). We interpret the orbicules as Ca-rich hybrid melts produced from limestone assimilation that did not homogenize with the host dike magma and underwent crystallization during rapid ascent, possibly propelled by the excess CO.sub.2. Our results inform on the amount and mechanism of CO.sub.2 transport at low crustal pressures ( 1.16 Tg CO.sub.2/year during its ~ 34 Myr lifespan.